Penyuluhan Kecerdasan Emosional Sebagai Upaya Pencegahan Tawuran dan Kekerasan Seksual di Kalangan Pelajar di Kota Palembang - Oktaviana, Rina; Cantika, Deya (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2025)
The aim of this community service activity is to prevent brawls and sexual violence which are often experienced by students, both at the junior and senior high school levels. With this outreach, it is hoped that it can help prevent delinquency that occurs among students, as well as provide them with an understanding of the negative impacts of acts of violence and brawls. Apart from that, it is hoped that students can better understand the importance of emotional intelligence in managing feelings and resolving conflicts without violence. The method used in this activity is an interactive lecture. As a result, counseling about emotional intelligence (EQ) can be an effective effort to prevent brawls and sexual violence among students.